2002
DOI: 10.2174/1389201023378120
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Folding Problem: A Biophysical Enigma

Abstract: Protein folding, the problem of how an amino acid sequence folds into a unique three-dimensional shape, has been a long-standing problem in biology. The success of genome-wide sequencing efforts has increased the interest in understanding the protein folding enigma, because realizing the value of the genomic sequences rests on the accuracy with which the encoded gene products are understood. Although a complete understanding of the kinetics and thermodynamics of protein folding has remained elusive, there has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 201 publications
(276 reference statements)
0
8
0
Order By: Relevance
“…Numerous research labs have demonstrated that proteins with equivalent amino acid sequences should fold into the same tertiary structure 22–26. While the Epoetin alfa from Epogen and Eprex have the same amino acid sequence, we detected differences in their biophysical characteristics.…”
Section: Discussionmentioning
confidence: 70%
“…Numerous research labs have demonstrated that proteins with equivalent amino acid sequences should fold into the same tertiary structure 22–26. While the Epoetin alfa from Epogen and Eprex have the same amino acid sequence, we detected differences in their biophysical characteristics.…”
Section: Discussionmentioning
confidence: 70%
“…Even more importantly, such combined MD approaches enhance substantially the efficiency of sampling for protein conformational space, leading to their applications in ab initio folding, investigating the protein folding mechanism, and constructing the FEL of the protein-solvent system. For details, refer to (Fetrow et al, 2002; Henzler-Wildman & Kern, 2007; Liu et al, 2012). …”
Section: Part I: Case Studies On Dynamics and Molecular Motions Of Prmentioning
confidence: 99%
“…Consequently, computational solution to the prediction of protein structure becomes the subject of intense activity. The computational structural prediction methodologies are often divided into three main categories: comparative modeling, fold recognition or threading, and ab initio folding methods (Fetrow, Giammona, Kolinski, & Skolnick, 2002). These methods involve the development of an energy function capable of identifying the most stable conformation of a protein and a scoring function for evaluating the predicted models.…”
Section: Introductionmentioning
confidence: 99%
“…Computational approaches to predict protein three-dimensional conformations are usually classified as homology modeling (or comparative modeling), fold recognition (or threading) and folding ab initio (see, for example, [18]). …”
Section: Computational Approaches To Protein Fold Predictionmentioning
confidence: 99%